Spherical fuzzy analytic hierarchy process (AHP) and its application to industrial robot selection - Kahraman, Cengiz; GÜNDOĞDU, FATMA KUTLU (My University, 2019)
The extensions of ordinary fuzzy sets such as intuitionistic fuzzv sets (IFS). Pythagorean fuzzy sets (PFS). and neutrosophic sets (NS). whose mem bership functions are based on three dimensions, aim at collecting experts' judg ments more informatively and explicitly. In the literature, generalized three-di mensional spherical fuzzy sets have been introduced by Kutlu Gündoğdu and Kahraman [2]. including their arithmetic operations, aggregation operators, and defuzzfication operations. In this paper, we develop and use spherical fuzzy’ an alytic hierarchy process (AHP) and apply it to an industrial robot selection problem.
Keywords: Spherical Fuzzy AHP; Industrial Robot Selection; Spherical Fuzzy Sets